2016
DOI: 10.1021/acs.jpclett.6b01147
|View full text |Cite
|
Sign up to set email alerts
|

Ultrabroad Photoluminescence and Electroluminescence at New Wavelengths from Doped Organometal Halide Perovskites

Abstract: Doping of semiconductors by introducing foreign atoms enables their widespread applications in microelectronics and optoelectronics. We show that this strategy can be applied to direct bandgap lead-halide perovskites, leading to the realization of ultrawide photoluminescence (PL) at new wavelengths enabled by doping bismuth (Bi) into lead-halide perovskites. Structural and photophysical characterization reveals that the PL stems from one class of Bi doping-induced optically active center, which is attributed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
77
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(85 citation statements)
references
References 51 publications
6
77
0
Order By: Relevance
“…Due to the ultrahigh gain, photocarrier excitation from valence band to the trap states within the perovskite bandgap can induce sizeable NIR photoresponse . Specifically, doping perovskites with proper foreign atoms can introduce appropriate trap/defect states within their bandgaps . In addition, incorporating narrow bandgap conjugated polymers or colloidal QDs into perovskite films is also a helpful technique to realize NIR photoresponse .…”
Section: Discussionmentioning
confidence: 99%
“…Due to the ultrahigh gain, photocarrier excitation from valence band to the trap states within the perovskite bandgap can induce sizeable NIR photoresponse . Specifically, doping perovskites with proper foreign atoms can introduce appropriate trap/defect states within their bandgaps . In addition, incorporating narrow bandgap conjugated polymers or colloidal QDs into perovskite films is also a helpful technique to realize NIR photoresponse .…”
Section: Discussionmentioning
confidence: 99%
“…For lead cation site, in both bulk and nanocrystalline forms, color‐tuning by partial lead substitution during the synthesis has been proven successful. Bi (III)‐doped organometal halide perovskites films exhibit edultra wide emission spectra in the near infrared region (850–1600 nm) 10. Mn (II)‐doped lead chloride perovskite NCs possess dual‐color emission 11.…”
Section: Introductionmentioning
confidence: 99%
“…[35][36][37][38][39] In general, new energy states within the band gap are introduced by doping, so as to facilitate the occurrence of low-energy electronic transitions. 35,40,41 MAPbX 3 are primarily doped by the elements isovalent with cations (Li + /Na + /Rb + ), anions (I À / Cl À ) or metal cations (Pb 2+ /M 2+ , M 2+ ¼ Sn 2+ , Sr 2+ , Cd 2+ , Zn 2+ or Ca 2+ ). 9,34,[42][43][44][45][46][47] In lead halide perovskites, MA and Pb cations are surrounded by 12 and 6 halide anions, respectively, which makes it to be a superb candidate to accommodate a variety of foreign ions with ionic radii comparable that of MA or Pb.…”
Section: Introductionmentioning
confidence: 99%
“…39 The previous work reported that the ions (Bi 3+ , Li + , Na + , K + , Rb + ) are doped into the halide perovskites, just as a topotactic insertion. 38,39,41,42,48 On one hand, the successfully incorporating dopants into perovskite crystals, and preserving the host lattice structures simultaneously, only cause tiny lattice distortion. On the other hand, these dopants oppose oxidation and reduction owing to their stability or resistance hence are chosen to be the positive additive.…”
Section: Introductionmentioning
confidence: 99%